Mathieu Functions and Hill’s Equation - 28.4 Fourier Series
DLMF | Formula | Constraints | Maple | Mathematica | Symbolic Maple |
Symbolic Mathematica |
Numeric Maple |
Numeric Mathematica |
---|---|---|---|---|---|---|---|---|
28.4.E1 | \Mathieuce{2n}@{z}{q} = \sum_{m=0}^{\infty}A^{2n}_{2m}(q)\cos@@{2mz} |
|
MathieuCE(2*n, q, z) = sum((A[2*m])^(2*n)(q)* cos(2*m*z), m = 0..infinity)
|
MathieuC[2*n, q, z] == Sum[(Subscript[A, 2*m])^(2*n)[q]* Cos[2*m*z], {m, 0, Infinity}, GenerateConditions->None]
|
Failure | Failure | Skipped - Because timed out | Skipped - Because timed out |
28.4.E2 | \Mathieuce{2n+1}@{z}{q} = \sum_{m=0}^{\infty}A^{2n+1}_{2m+1}(q)\cos@@{(2m+1)z} |
|
MathieuCE(2*n + 1, q, z) = sum((A[2*m + 1])^(2*n + 1)(q)* cos((2*m + 1)*z), m = 0..infinity)
|
MathieuC[2*n + 1, q, z] == Sum[(Subscript[A, 2*m + 1])^(2*n + 1)[q]* Cos[(2*m + 1)*z], {m, 0, Infinity}, GenerateConditions->None]
|
Failure | Failure | Skipped - Because timed out | Skipped - Because timed out |
28.4.E3 | \Mathieuse{2n+1}@{z}{q} = \sum_{m=0}^{\infty}B^{2n+1}_{2m+1}(q)\sin@@{(2m+1)z} |
|
MathieuSE(2*n + 1, q, z) = sum((B[2*m + 1])^(2*n + 1)(q)* sin((2*m + 1)*z), m = 0..infinity)
|
MathieuS[2*n + 1, q, z] == Sum[(Subscript[B, 2*m + 1])^(2*n + 1)[q]* Sin[(2*m + 1)*z], {m, 0, Infinity}, GenerateConditions->None]
|
Failure | Failure | Skipped - Because timed out | Skipped - Because timed out |
28.4.E4 | \Mathieuse{2n+2}@{z}{q} = \sum_{m=0}^{\infty}B^{2n+2}_{2m+2}(q)\sin@@{(2m+2)z} |
|
MathieuSE(2*n + 2, q, z) = sum((B[2*m + 2])^(2*n + 2)(q)* sin((2*m + 2)*z), m = 0..infinity)
|
MathieuS[2*n + 2, q, z] == Sum[(Subscript[B, 2*m + 2])^(2*n + 2)[q]* Sin[(2*m + 2)*z], {m, 0, Infinity}, GenerateConditions->None]
|
Failure | Failure | Skipped - Because timed out | Skipped - Because timed out |
28.4#Ex1 | aA_{0}-qA_{2} = 0 |
|
a*A[0]- q*A[2] = 0 |
a*Subscript[A, 0]- q*Subscript[A, 2] == 0 |
Skipped - no semantic math | Skipped - no semantic math | - | - |
28.4#Ex2 | (a-4)A_{2}-q(2A_{0}+A_{4}) = 0 |
|
(a - 4)*A[2]- q*(2*A[0]+ A[4]) = 0 |
(a - 4)*Subscript[A, 2]- q*(2*Subscript[A, 0]+ Subscript[A, 4]) == 0 |
Skipped - no semantic math | Skipped - no semantic math | - | - |
28.4#Ex3 | (a-4m^{2})A_{2m}-q(A_{2m-2}+A_{2m+2}) = 0 |
(a - 4*(m)^(2))*A[2*m]- q*(A[2*m - 2]+ A[2*m + 2]) = 0 |
(a - 4*(m)^(2))*Subscript[A, 2*m]- q*(Subscript[A, 2*m - 2]+ Subscript[A, 2*m + 2]) == 0 |
Skipped - no semantic math | Skipped - no semantic math | - | - | |
28.4#Ex4 | (a-1-q)A_{1}-qA_{3} = 0 |
|
(a - 1 - q)*A[1]- q*A[3] = 0 |
(a - 1 - q)*Subscript[A, 1]- q*Subscript[A, 3] == 0 |
Skipped - no semantic math | Skipped - no semantic math | - | - |
28.4#Ex5 | \left(a-(2m+1)^{2}\right)A_{2m+1}-q(A_{2m-1}+A_{2m+3}) = 0 |
(a -(2*m + 1)^(2))*A[2*m + 1]- q*(A[2*m - 1]+ A[2*m + 3]) = 0 |
(a -(2*m + 1)^(2))*Subscript[A, 2*m + 1]- q*(Subscript[A, 2*m - 1]+ Subscript[A, 2*m + 3]) == 0 |
Skipped - no semantic math | Skipped - no semantic math | - | - | |
28.4#Ex6 | (a-1+q)B_{1}-qB_{3} = 0 |
|
(a - 1 + q)*B[1]- q*B[3] = 0 |
(a - 1 + q)*Subscript[B, 1]- q*Subscript[B, 3] == 0 |
Skipped - no semantic math | Skipped - no semantic math | - | - |
28.4#Ex7 | \left(a-(2m+1)^{2}\right)B_{2m+1}-q(B_{2m-1}+B_{2m+3}) = 0 |
(a -(2*m + 1)^(2))*B[2*m + 1]- q*(B[2*m - 1]+ B[2*m + 3]) = 0 |
(a -(2*m + 1)^(2))*Subscript[B, 2*m + 1]- q*(Subscript[B, 2*m - 1]+ Subscript[B, 2*m + 3]) == 0 |
Skipped - no semantic math | Skipped - no semantic math | - | - | |
28.4#Ex8 | (a-4)B_{2}-qB_{4} = 0 |
|
(a - 4)*B[2]- q*B[4] = 0 |
(a - 4)*Subscript[B, 2]- q*Subscript[B, 4] == 0 |
Skipped - no semantic math | Skipped - no semantic math | - | - |
28.4#Ex9 | (a-4m^{2})B_{2m}-q(B_{2m-2}+B_{2m+2}) = 0 |
(a - 4*(m)^(2))*B[2*m]- q*(B[2*m - 2]+ B[2*m + 2]) = 0 |
(a - 4*(m)^(2))*Subscript[B, 2*m]- q*(Subscript[B, 2*m - 2]+ Subscript[B, 2*m + 2]) == 0 |
Skipped - no semantic math | Skipped - no semantic math | - | - | |
28.4.E9 | 2\left(A^{2n}_{0}(q)\right)^{2}+\sum_{m=1}^{\infty}\left(A^{2n}_{2m}(q)\right)^{2} = 1 |
|
2*((A[0])^(2*n)(q))^(2)+ sum(((A[2*m])^(2*n)(q))^(2), m = 1..infinity) = 1 |
2*((Subscript[A, 0])^(2*n)[q])^(2)+ Sum[((Subscript[A, 2*m])^(2*n)[q])^(2), {m, 1, Infinity}, GenerateConditions->None] == 1 |
Skipped - no semantic math | Skipped - no semantic math | - | - |
28.4.E10 | \sum_{m=0}^{\infty}\left(A^{2n+1}_{2m+1}(q)\right)^{2} = 1 |
|
sum(((A[2*m + 1])^(2*n + 1)(q))^(2), m = 0..infinity) = 1 |
Sum[((Subscript[A, 2*m + 1])^(2*n + 1)[q])^(2), {m, 0, Infinity}, GenerateConditions->None] == 1 |
Skipped - no semantic math | Skipped - no semantic math | - | - |
28.4.E11 | \sum_{m=0}^{\infty}\left(B^{2n+1}_{2m+1}(q)\right)^{2} = 1 |
|
sum(((B[2*m + 1])^(2*n + 1)(q))^(2), m = 0..infinity) = 1 |
Sum[((Subscript[B, 2*m + 1])^(2*n + 1)[q])^(2), {m, 0, Infinity}, GenerateConditions->None] == 1 |
Skipped - no semantic math | Skipped - no semantic math | - | - |
28.4.E12 | \sum_{m=0}^{\infty}\left(B^{2n+2}_{2m+2}(q)\right)^{2} = 1 |
|
sum(((B[2*m + 2])^(2*n + 2)(q))^(2), m = 0..infinity) = 1 |
Sum[((Subscript[B, 2*m + 2])^(2*n + 2)[q])^(2), {m, 0, Infinity}, GenerateConditions->None] == 1 |
Skipped - no semantic math | Skipped - no semantic math | - | - |
28.4#Ex10 | A^{0}_{0}(0) = 1/\sqrt{2},\quad A^{2n}_{2n}(0) |
(A[0])^(0)(0) = 1/(sqrt(2)) |
(Subscript[A, 0])^(0)[0] == 1/(Sqrt[2]) |
Skipped - no semantic math | Skipped - no semantic math | - | - | |
28.4#Ex11 | A^{2n}_{2m}(0) = 0 |
(A[2*m])^(2*n)(0) = 0 |
(Subscript[A, 2*m])^(2*n)[0] == 0 |
Skipped - no semantic math | Skipped - no semantic math | - | - | |
28.4#Ex12 | A^{2n+1}_{2n+1}(0) = 1 |
|
(A[2*n + 1])^(2*n + 1)(0) = 1 |
(Subscript[A, 2*n + 1])^(2*n + 1)[0] == 1 |
Skipped - no semantic math | Skipped - no semantic math | - | - |
28.4#Ex13 | A^{2n+1}_{2m+1}(0) = 0 |
(A[2*m + 1])^(2*n + 1)(0) = 0 |
(Subscript[A, 2*m + 1])^(2*n + 1)[0] == 0 |
Skipped - no semantic math | Skipped - no semantic math | - | - | |
28.4#Ex14 | B^{2n+1}_{2n+1}(0) = 1 |
|
(B[2*n + 1])^(2*n + 1)(0) = 1 |
(Subscript[B, 2*n + 1])^(2*n + 1)[0] == 1 |
Skipped - no semantic math | Skipped - no semantic math | - | - |
28.4#Ex15 | B^{2n+1}_{2m+1}(0) = 0 |
(B[2*m + 1])^(2*n + 1)(0) = 0 |
(Subscript[B, 2*m + 1])^(2*n + 1)[0] == 0 |
Skipped - no semantic math | Skipped - no semantic math | - | - | |
28.4#Ex16 | B^{2n+2}_{2n+2}(0) = 1 |
|
(B[2*n + 2])^(2*n + 2)(0) = 1 |
(Subscript[B, 2*n + 2])^(2*n + 2)[0] == 1 |
Skipped - no semantic math | Skipped - no semantic math | - | - |
28.4#Ex17 | B^{2n+2}_{2m+2}(0) = 0 |
(B[2*m + 2])^(2*n + 2)(0) = 0 |
(Subscript[B, 2*m + 2])^(2*n + 2)[0] == 0 |
Skipped - no semantic math | Skipped - no semantic math | - | - | |
28.4.E17 | A^{2n}_{2m}(-q) = (-1)^{n-m}A^{2n}_{2m}(q) |
|
(A[2*m])^(2*n)(- q) = (- 1)^(n - m)* (A[2*m])^(2*n)(q) |
(Subscript[A, 2*m])^(2*n)[- q] == (- 1)^(n - m)* (Subscript[A, 2*m])^(2*n)[q] |
Skipped - no semantic math | Skipped - no semantic math | - | - |
28.4.E18 | B^{2n+2}_{2m+2}(-q) = (-1)^{n-m}B^{2n+2}_{2m+2}(q) |
|
(B[2*m + 2])^(2*n + 2)(- q) = (- 1)^(n - m)* (B[2*m + 2])^(2*n + 2)(q) |
(Subscript[B, 2*m + 2])^(2*n + 2)[- q] == (- 1)^(n - m)* (Subscript[B, 2*m + 2])^(2*n + 2)[q] |
Skipped - no semantic math | Skipped - no semantic math | - | - |
28.4.E19 | A^{2n+1}_{2m+1}(-q) = (-1)^{n-m}B^{2n+1}_{2m+1}(q) |
|
(A[2*m + 1])^(2*n + 1)(- q) = (- 1)^(n - m)* (B[2*m + 1])^(2*n + 1)(q) |
(Subscript[A, 2*m + 1])^(2*n + 1)[- q] == (- 1)^(n - m)* (Subscript[B, 2*m + 1])^(2*n + 1)[q] |
Skipped - no semantic math | Skipped - no semantic math | - | - |
28.4.E20 | B^{2n+1}_{2m+1}(-q) = (-1)^{n-m}A^{2n+1}_{2m+1}(q) |
|
(B[2*m + 1])^(2*n + 1)(- q) = (- 1)^(n - m)* (A[2*m + 1])^(2*n + 1)(q) |
(Subscript[B, 2*m + 1])^(2*n + 1)[- q] == (- 1)^(n - m)* (Subscript[A, 2*m + 1])^(2*n + 1)[q] |
Skipped - no semantic math | Skipped - no semantic math | - | - |